Simple human counting system with LoRa integration - Koh, Ji Sheng (2019)
The Internet of Things (IoT) is a smart network of devices, ranging from small household electrical appliances to larger objects such as cars and buses. These “Smart” objects are built containing special hardware and software such as actuators and sensors, and have network connectivity capabilities, allowing them to communicate with one another and to collect data for exchanging. It is a technological advancement that is widely utilized in many industries around the world today. The purpose of this project is to create a product which can be used in day to day applications and be integrated with the Internet of Things using a Low-Powered Wide Area Network (LPWAN) Technology called Long Range or LoRa for short. The planned product for this project utilizes a Raspberry Pi computer, thermal camera and wireless communication chip in order to produce a human counting device that can be applied in areas which require such data in order to optimize efficiency of operations or for any other purposes.